Pengaruh Motivasi Pribadi, Komitmen Kuat dan Manajemen Waktu Terhadap Displin Kerja Pelaku Wirausaha di Destinasi Wisata Situ Cipondoh Kota Tangerang, Provinsi Banten - Herienda, Florensia; Hendradewi, Savitri; Dewi, Triana Rosalina; Nurtanio, Tessina Liliani (Jurnal Ilmiah Pariwisata, 2023)
This study aims to determine the effect of personal motivation, strong commitment and time management on work discipline. This type of research is descriptive research with a quantitative approach with multiple regression analysis using Smart PLS. The location of this research was carried out in the tourist destination Situ Cipondoh. The sampling technique uses saturated sampling because the total population is the same as the number of samples, namely 63 entrepreneurs in the Situ Cipondoh tourist destination. The results of the study partially show that personal motivation, strong commitment and time management have a significant effect on work discipline. Personal motivation in business actors strengthens energy, intrinsic drive, focus, perseverance, and consistency, and encourages self-development and increases overall business success. Strong commitment to business actors is an important factor in building and maintaining high work discipline in the business world and encourages an attitude of responsibility, resilience, consistency and high motivation, all of which contribute to business success and growth. Good time management helps businesses identify important tasks, create a structured schedule, increase efficiency, reduce stress and improve the quality of their work, all of which contribute to productivity and business success. Keywords: Personal Motivation, Strong Commitment, Time Management, Work Discipline